Pharmacokinetics and Safety of Marqibo (Vincristine Sulfate Liposomes Injection) in Cancer Patients With Impaired Liver Function - Bedikian, Agop Y.; Silverman, Jeffrey A.; Papadopoulos, Nicholas E.; Kim, Kevin B.; Hagey, Anne E.; Vardeleon, Anna; Hwu, Wen-Jen; Homsi, Jade; Davies, Michael; Hwu, Patrick (Journal of clinical pharmacology, 2011)
Marqibo (vincristine sulfate liposome injection, VSLI) is a novel liposomal formulation of vincristine sulfate (VCR) being developed for the systemic treatment of cancer. This study evaluated the pharmacokinetics (PK) of Marqibo in subjects with melanoma and impaired hepatic function. Calculated PK parameters were similar in subjects with impaired liver function compared with those in subjects with adequate liver function. Subjects with impaired liver function universally had a monoexponential total plasma VCR concentration versus time decline, whereas two thirds of subjects with adequate liver function had a biexponential decline profile. Because one third of subjects with normal hepatic function demonstrated monoexponential disposition, lack of biexponential disposition in the hepatically impaired subjects cannot be clearly attributed to liver impairment. VSLI was generally well tolerated in all subjects.